MENGKONTEKSTUALISASIKAN HADITS TARBAWI BAGI PENDIDIKAN ISLAM DI ERA 4.0 - Moh Sholihul Anshori; Ashif Az Zafi (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2020)
Educational development always cannges and has now arrieved at an era known as the era 4.0. But  with these developments new callenges arise for Islamic education in this era, namely the moral values of studens and the develovepment of the world of Islamic education wich now seems to be left behind from the west. Then it must be immediately found the right way to deliver teaching Islamic education right now. Namely by using a hadith in wich quality is known , then to be able to maximaze the hadith is by contextualiing it. general religion. So by contextualizing the students will be invited to think actively and have a more real picture and certainly more effective than  ( conventional ) metdhos.